In situ conductance monitoring of Pt thin film growth by area-selective atomic layer deposition. Issue 2 (4th October 2017) - Prima, Giorgia Di; Sachser, Roland; Gruszka, Peter; Hanefeld, Marc; Halbritter, Thomas; Heckel, Alexander; Huth, Michael
Abstract: In situ monitoring of thin film growth on the lateral nanoscale provides insight into different growth stages and establishes a basis for feedback-controlled optimization of the growth process. Here we present a novel approach towards in situ monitoring of area-selective atomic layer deposition of metals, in particular platinum, using the electrical conductance of the growing layer as probed quantity. Area-selectivity is reached by thin platinum seed layers fabricated by focused electron beam induced deposition (FEBID). Different growth stages are identified by their respective impact on the conductance. The growth rate is optimized in a feedback-loop that controls the cycling periods of the atomic layer deposition process employing a genetic algorithm. Our approach is sufficiently general to be applicable to a large variety of other deposition setups that do not use FEBID for seeding.